2022
DOI: 10.1109/tgrs.2021.3099896
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation-Based Error Budget of the TES Method for the Design of the Spectral Configuration of the Micro-Bolometer-Based MISTIGRI Thermal Infrared Sensor

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
3
3
0
Order By: Relevance
“…2. Our results are similar to those reported for the MISTIGRI mission with spectral configurations that di↵er from the TRISHNA reference (Jacob et al, 2021). Therefore, scanning the spectral space for each of the four channel is likely to provide similar results than scanning the spectral space using separated pairs of channels.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…2. Our results are similar to those reported for the MISTIGRI mission with spectral configurations that di↵er from the TRISHNA reference (Jacob et al, 2021). Therefore, scanning the spectral space for each of the four channel is likely to provide similar results than scanning the spectral space using separated pairs of channels.…”
Section: Discussionsupporting
confidence: 84%
“…This main dependency to atmospheric conditions, which implies that the TES sensitivity to channel positions within atmospheric windows is moderate, hints that sliding at the same time the four TRISHNA TIR channels is likely to provide similar results on TES performance as obtained in this study, as well as similar recommendations for an optimized TRISHNA spectral configuration, provided that TRISHNA channels are not located nearby the limits of the atmospheric window. This statement is also supported by the similarity between the results of the current study and those reported for the MISTIGRI mission (Jacob et al, 2021) with di↵erent spectral configurations including more than two channels.…”
Section: On the Tir1/tir2 And Tir3/tir4 Pairs Separationsupporting
confidence: 89%
See 3 more Smart Citations